Breathing Micelles for Combinatorial Treatment of Rheumatoid Arthritis. (13th October 2020) - Tao, Siyue; Cheng, Jian; Su, Gai; Li, Dan; Shen, Zhiqiang; Tao, Fenghua; You, Tao; Hu, Jinming
Abstract: Breathing process involves inhalation and exhalation of different gases in animals. The gas exchange of the breathing process plays a critical role in maintaining the physiological functions of living organisms. Although artificial breathing materials exhibiting volume expansion and contraction upon alternate exposure to different gases have been well explored, those being able to realize the gas exchange remain elusive. Herein, we report breathing micelles (BM) capable of inhaling nitric oxide (NO) and exhaling carbon monoxide (CO), both of which are endogenous gaseous signaling molecules. We demonstrate that BM can simultaneously scavenge overproduced NO and attenuate proinflammatory cytokines in lipopolysaccharide (LPS)‐challenged macrophage cells. In vivo studies revealed that BM outperformed conventional nonsteroidal anti‐inflammatory drugs such as dexamethasone (Dexa) in treatment of rheumatoid arthritis (RA) in adjuvant‐induced arthritis (AIA) rats, likely due to the combinatorial effect of NO depletion, CO‐mediated deactivation of inducible NO synthase (iNOS) and activation of heme oxygenase‐1 (HO‐1). This work provides new insights into artificial BM for potential biomedical applications. Abstract : Breathing micelles (BM) that can inhale nitric oxide and exhale carbon monoxide under visible light irradiation were developed. The BM can not only scavenge the overproduced nitrite but also attenuate proinflammatory cytokines in both LPS‐challenged macrophage cells and adjuvant‐induced arthritis rats, showing a combinatorial anti‐inflammatory performance better than any of the single ingredients of the BM and dexamethasone.